Von Recklinghausen disease with recurrent hip dislocation and Osteonecrosis. Case presentation - Rolando Dornes Ramon; Yordany Vázquez Mora; Aimé Alberna Cardoso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Von Recklinghausen disease (neurofibromatosis type 1) is one of the most common autosomal dominant diseases which affect humans. The most frequent skeletal alteration is kyphoscoliosis (due to vertebral dysplasia), which can be progressive and accompanied by restrictive type respiratory problems or cardiac alterations. Hip dislocation associated with neurofibromatosis type 1 is very rare, as is osteonecrosis. The different modalities of imaging studies play an important role in the diagnosis and monitoring of this nosological entity. Due to the rare occurrence of hip dislocation with osteonecrosis associated with neurofibromatosis type 1, it was decided to present the case of a 47-year-old white patient.